2000
DOI: 10.1021/ol005639m
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport Limitations Reduce the Effective Stereospecificity in Enzyme-Catalyzed Kinetic Resolution

Abstract: [reaction-see text] The kinetic resolution of seudenol catalyzed by Candida antarctica lipase B in hexane was investigated. Large differences in reaction rate and stereospecificity were observed when different enzyme preparations were used. These differences were ascribed to mass transport limitations which reduced both reaction rate and stereospecificity. Lyophilized enzyme preparations were more apt to give this problem than immobilized preparations. Further, low substrate concentrations enhanced the effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…However, it is more likely that the large surface area of the buffer layer in the aqua gels enhances phase transfer of benzaldehyde ( 11a ) and mandelonitrile ( 2a ). As already observed earlier, enhancement of the performance of an enzyme upon immobilization is not always due to an improved action of the enzyme [30] .…”
Section: Encapsulation 31supporting
confidence: 62%
See 1 more Smart Citation
“…However, it is more likely that the large surface area of the buffer layer in the aqua gels enhances phase transfer of benzaldehyde ( 11a ) and mandelonitrile ( 2a ). As already observed earlier, enhancement of the performance of an enzyme upon immobilization is not always due to an improved action of the enzyme [30] .…”
Section: Encapsulation 31supporting
confidence: 62%
“…On this carrier its stereoselectivity and activity is even better than when immobilized as Novozym 435. However, it is also stated that diffusion effects need to be taken into account, emphasizing that there can always be more than one reason why an enzyme performs better/worse when modifying the carrier and that the improvements seen might actually have nothing to do with the carrier [30] . Indeed, Novozym 435 and free CALB were more recently shown to have identical stereoselectivity [31] .…”
Section: Adsorption/electrostatic Interactions 23mentioning
confidence: 99%
“…[32] It is [a] The titrations were performed for 24 h in hexane/diethyl ether (97:3) at a water activity (a w ) 0. 33 thus likely that mass transfer limitations influenced the relative rates of the conversion of the two enantiomers of 1-phenylethanol.…”
Section: Thermomyces Lanuginosus Lipase Immobilised Onto Porous Polypmentioning
confidence: 99%
“…Better access to the enzyme molecules could also be the reason for the increment of enantioselectivity induced by all the sugars tested (Table 5.3 ). In fact, Rottici et al [22] showed that immobilized CALB (e.g. Novozym 435), in which the substrate should be less hindered in reaching the catalytic active site, has both higher activity and enantioselectivity with respect to other enzyme preparations (e.g.…”
Section: Why Do Additives Affect the Activity And Enantioselectivity mentioning
confidence: 99%